An Experimental Study of Recall and Precision Rates in Retrieval of Text Documents Using Different Distance Measures - Patki, US; Kurhe, AB; Khot, PG (International Journal of Computer Sciences and Engineering, 2025)
Searching is the most important process in an information retrieval from available large databases. Many times we search for a set of documents which is relevant to the given search document. Text mining helps us to mine the information from a given set of documents and it is most popular technique in Information retrieval. In this research paper we have applied distinct distance measures for retrieval of most similar documents to the queried document from a set of given document. For obtaining optimality for required search, we have gone through pre-processing of documents, creating vector space model and used distance measure techniques. Precision and recall are the basic measures used in evaluating search strategies. We have presented five distance measure technique applied on hundred text documents from standard database 20NewsGroup and calculated Recall and precision rate for text documents retrieval. We have used MatLab 10a as a development tool for our experiment.